Spiritual Beliefs of Jordanian Adult Patients Receiving Palliative Care - Fawares, Fadi (Journal of religion and health, 2021)
This study aimed to explore spiritual beliefs held by Jordanian patients receiving palliative care. In order to accomplish this aim, three objectives were specified: 1) identify the spiritual beliefs of adult patients receiving palliative care, 2) to develop an Arabic version of the beliefs and values scale, and 3) to identify the perception of spirituality of adult patients receiving palliative care. Cross-sectional descriptive research design was used to describe the spiritual beliefs. The response rate was 70%; non-probability convenience sampling method was used for (N = 119) adult palliative patients who are receiving care at specialized oncology Center in Jordan. The findings revealed that the spirituality religious beliefs aspect total mean score (3.38 ± .33) was higher than the spirituality non-religious beliefs aspect total mean score (2.49 ± .50). There was a significant impact on enhancing spirituality score with patient who had attended a course about spirituality (p = .007) or had been visited by religious adviser (p = .022). Statistically significant differences were found between the religious beliefs score and age (p = .014), educational level (p = .015), and the patient who had attended a course about spirituality (p = .27). The conceptualizations of spirituality highly cultural are marked, and it differs from populations to others; it appears that spirituality among Middle East population is different than Western populations.